Challenges in Teaching Physics in Inclusive Classrooms: Insights from Secondary Physics Teachers - Atika, Iva Nandya; Wulandary, Verra; Vivialina, Adhelia Dwi (Impulse: Journal of Research and Innovation in Physics Education, 2026)
The universal right to science education aims to provide equal opportunities for all students, including those with special educational needs (SEN). However, implementing inclusive practices in physics classrooms remains challenging due to the abstract and cognitively demanding nature of physics concepts. This study explores how inclusive physics teaching is implemented in secondary schools and examines the challenges faced by teachers in inclusive classroom settings. A qualitative phenomenological design was employed to explore the lived experiences of five secondary physics teachers from public and private inclusive schools in the Special Region of Yogyakarta, Indonesia. Data were collected through semi-structured interviews and analyzed thematically within a phenomenological framework to explore recurring meanings and experiences related to inclusive physics teaching. The findings reveal that inclusive physics teaching is implemented through three interconnected dimensions: conceptual accessibility, instructional flexibility, and assessment adaptation. Teachers support diverse learners by contextualizing abstract concepts, using multimodal and collaborative strategies, and applying flexible assessment practices. These approaches reflect alignment with the principles of Universal Design for Learning (UDL) and inclusive pedagogy. However, the implementation remains largely intuitive and context-dependent. The study also identifies significant challenges, including limited professional training, time constraints, insufficient instructional resources, lack of support personnel, and socio-cultural factors such as peer acceptance and parental involvement. Additional issues, such as classroom complexity and inconsistent student attendance, further affect teaching effectiveness. These findings highlight the need for stronger systemic support, including teacher professional development, accessible learning resources, and collaborative partnerships, to enhance inclusive physics teaching practices.